Brazilian red propolis reduces orange-complex periodontopathogens growing in multispecies biofilms. Issue 3 (16th March 2019) - Miranda, Stela Lima Farias; Damasceno, Jennifer Toledo; Faveri, Marcelo; Figueiredo, Luciene; da Silva, Helio Doyle; Alencar, Severino Matias de Alencar; Rosalen, Pedro Luiz; Feres, Magda; Bueno-Silva, Bruno
Abstract: This study investigated the antimicrobial effects of the ethanolic extract of Brazilian red propolis (BRP) on multispecies biofilms. A seven-day-old subgingival biofilm with 32 species was grown in a Calgary device. Biofilms were treated with BRP (1, 600, 800, 400 and 200 μg ml −1 ) twice a day for 1 min, starting from day 3. Chlorhexidine (0.12%) and dilution-vehicle were used as positive and negative controls, respectively. On day 7, metabolic activity and the microbial composition of the biofilms by DNA-DNA hybridization were determined. The viability data were analyzed by one-way ANOVA followed by Tukey's post hoc, whereas the microbial composition data were transformed via BOX-COX and analyzed using Dunnett's post hoc . BRP (1, 600 μg ml −1 ) decreased biofilm metabolic activity by 45%, with no significant difference from chlorhexidine-treated samples. BRP (1, 600 μg ml −1 ) and chlorhexidine significantly reduced levels of 14 bacterial species compared to the vehicle control. Taken together, BRP showed promising antimicrobial properties which may be useful in periodontal disease control.